Sustainability of Islamic Banking in the Midst of Global Economy: Case Study in Indonesia - Setya Pramono; M. Miftahul Qolbi; Arinal Haqqi; Arinal Haqqo (International Journal of Economics, Management and Accounting, 2024)
Sharia banking is a bank whose activities refer to Islamic law and in its activities neither charges interest nor pays interest to customers. Sharia bank rewards received or paid to customers depend on the contracts and agreements entered into by the customer and the bank. Agreements (contracts) contained in sharia banking must comply with the terms and pillars of the contract as regulated in Islamic sharia. Over the last decade, the Islamic banking industry has developed very rapidly, not only the number of Sharia Commercial Banks (BUS) but also their assets have increased several times to hundreds of trillions. Seeing the current phenomenon of sharia banking is the author's interest in carrying out research. This research approach uses a descriptive approach, namely by obtaining data collection and data analysis aimed at creating systematic, current and accurate descriptions, depictions of the facts, as well as the relationships between the phenomena being investigated. The types and sources of data are quantitative data and secondary data taken from company reports. The results obtained are that Bank Syariah Indonesia is included in the very rapid development category. This is proven every year that he is able to achieve good goals and development. This shows that the public's response to trusting Indonesian Sharia banks is very good. And able to balance the challenges and opportunities in this current of globalization.